Study of phoconductive and electrical properties of AgInS2 thin films prepared by co-evaporation (2012)
AgInS 2 (AIS) thin films with chalcopyrite type tetragonal structure were grown using a procedure based on the co-evaporation of their precursors in a two stage process. The effect of the evaporated mass of Ag to evaporated mass of In (m Ag /m In ) ratio on the electrical transport properties was investigated through temperature dependent conductivity and Hall voltage measurements carried out in the range between 90K and 600K. The study revealed that the electrical conductivity of the AIS films is affected by hole transport in extended states of the valence band as well as by variable range hopping (VRH) transport mechanism. Transient photocurrent measurements, indicated that the electrical transport is affected by recombination processes via band to band transitions and trap assisted transitions, being the band to band recombination de dominant one. It was also found that the AgInS 2 thin films present p-type conductivity, a high absorption coefficient (greater than 10 4 cm -1 ) and an energy band gap E g of about 1.94 eV, indicating that this compound has good properties to perform as absorbent layer on the top cell in two junction tandem solar cells.